FACTORS IN RELIABILITY AS A REASON TO POLYGAMI ACCORDING TO ISLAMIC LAW AND POSITIVE LAW - Imam Hafas (Universitas Islam Negeri (UIN) Mataram, 2020)
The dynamics of polygamy are not uncommon to talk about, considering that polygamy is widely practiced by the public and the actions of polygamy are not in accordance with the existing laws and regulations or laws in Indonesia. Many actions of polygamy violate the existing rules, one of which is the existence of marriage outside the KUA conducted secretly. A family will never achieve happiness in the world without the descendants born from the bond of marriage. Indonesia is one country that is able to see and interpret the actions of polygamy that occur outside the court or without the knowledge of the first wife. This is triggered by the desire of a husband who wants to polygamy or gets married for the second time. Talking about a marriage that is not always happy, can even bring a disaster, both on the part of a wife and a husband. One way is to get offspring from the marriage. In scientific studies that will be the focal point is about the reason for a husband to carry out acts of polygamy, both in Islamic provisions and in the provisions of the law. The method in scientific studies here uses qualitative methods with normative juridical research types and the nature of descriptive analysis research, as well as using an inductive thinking framework.